Lessons learned from the Flagship 4 Results-based management Trial - Thornton, Philip K.; Förch, Wiebke; Cramer, Laura K.; Vasileiou, Ioannis; Jost, Christine; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Lessons learned from within CCAFS from the Flagship 4 results-based management trial.